Review of the grass feeding leafhopper genus Paramesodes Ishihara (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) from China - Duan, Yani; Zhang, Yalin (Zootaxa, 2012)
The Chinese leafhopper species of the genus Paramesodes Ishihara are revised, one new species P. cangshanae sp. n. is described and a key is provided for the five Chinese species in this genus.